Influence of laser ignition on characteristics of an engine for hydrogen enriched CNG and iso-octane usage. (26th October 2021) - Yontar, Ahmet Alper; Wong, Victor
Abstract: The study has focused on determining the laser plug effects on engine characteristics and the laser plug usage results have compared with spark plug usage. The laser ignition technique is a type of new ignition technique and an important solution that can make combustion systems more efficient. The testing of an engine with a laser plug is the novelty of the study and the tests were carried out with reference to equivalence ratio and plug power ranges. The behaviors of the engine at full load were examined so experimentally for both ignition techniques at hydrogen enriched CNG and iso-octane mixture usage. The tests were carried out for variations of 0.4–2.0 equivalence ratio and 20–120 W plug power. A mixture that 90% iso-octane and 10% HCNG in mass was used at two ignition modes in tests for 3300 rpm maximum engine torque speed. Also, the flame formation and propagation for both ignition techniques were detected via a high-speed camera. The tests have shown the laser ignition leads to more energy consumption in the rich mixture conditions and also, less energy is required in the lean conditions. The laser ignition discharge has extended the engine's lean combustion limits via a small energy input at the tests. The high-speed camera images have shown that the laser ignition reduces the Kernel flame formation and propagation time. The laser ignition technique was produced less NOx than the conventional spark ignition method. Highlights: Laser ignition effects on engine performance characteristics and emissions. The tests were carried out for iso-octane - HCNG mixture at maximum torque speed. Comparison of laser ignition effects with spark ignition for the flame formation. The laser ignition has lead to less energy is required in the lean conditions. The laser ignition technique has produced less NOx than the spark plug.